Educational Leaders' Perceptions and Uses of School Climate Data. Issue 4 (July 2022) - Debnam, Katrina J.; Edwards, Kelly; Maeng, Jennifer L.; Cornell, Dewey
National interest in using school climate as an accountability measure makes it important to understand how school leaders view and make use of school climate data. The purpose of this study was to investigate how school and district administrators use climate data in Virginia, where a statewide school climate survey is annually administered. School principals ( N  = 283) completed surveys concerning their use of the school climate results for their school. Simultaneously, semi-structured interviews were conducted with school division leaders and school administrators ( N  = 10) to deepen our understanding of how the school climate results were being used. Qualitative content analysis was used to identify patterns in the data. Study results reflect a consensus by educational leaders on the utility of receiving school climate data in order to make data-based decisions to improve outcomes for students. Participants provided thoughtful and constructive feedback on the importance of student relationships, perceptions of student subgroups, comparing their data with other schools, and ways to facilitate data-based decision-making. Participants also expressed a desire for additional support in understanding statistical results and generating recommendations for school improvement. These findings suggest that increasing the clarity and comprehensiveness of school climate data reports and providing support for interpreting the results will increase educational leaders' ability to use school climate surveys.